Introduction to logic - Copi, Irving M.; Cohen, Carl, 1931-; Rodych, Victor, 1958- (New York Routledge, 2019)
"For more than six decades, and for thousands of students, Introduction to Logic has been the gold standard in introductory logic texts. In this 15th Edition, Carl Cohen and Victor Rodych update Irving M. Copi's classic text, improving on its many strengths and introducing new and helpful material that will greatly assist both students and instructors"--
Basic logical concepts -- Analyzing arguments -- Language and definitions -- Fallacies -- Categorical propositions -- Categorical syllogisms -- Syllogisms in ordinary language -- Propositional logic I: truth-functional statements and arguments -- Propositional logic II: methods of deduction -- Predicate logic: quantification theory -- Analogical reasoning -- Causal reasoning -- Science and hypothesis -- Probability.
Includes index.
Keywords: Logic -- Textbooks